2020
DOI: 10.1155/2020/8855063
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Utilization of Light Energy in Semiclosed Greenhouse Using Three-Dimensional Cucumber Model

Abstract: In the east of China, low temperature and light energy in winter are the main factors for the decline in cucumber yield, as well as in greenhouses without supplementary light. Optimal utilization of light energy is critical to increase cucumber yield. In this study, experimental measurements were conducted in two scenarios, April to May (Apr-May) and November to December (Nov-Dec) 2015, respectively, to analyze leaf development, dry matter accumulation, and yield of cultivated cucumber. Statistical analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The visualization of 3D plant structures was produced by 'Visualization and 3D Reconstruction of Plant Models', a software developed by Shanghai Academy of Agricultural Sciences (Figure 2) [31]. The program filled the prepared leaf-shaped samples into the skeleton [31,38].…”
Section: Simulation Of 3d Structural Model 221 Data Collection and 3d...mentioning
confidence: 99%
See 2 more Smart Citations
“…The visualization of 3D plant structures was produced by 'Visualization and 3D Reconstruction of Plant Models', a software developed by Shanghai Academy of Agricultural Sciences (Figure 2) [31]. The program filled the prepared leaf-shaped samples into the skeleton [31,38].…”
Section: Simulation Of 3d Structural Model 221 Data Collection and 3d...mentioning
confidence: 99%
“…However, the position of the sun changed during the day, which affected the area of leaf surface intercepting the light at different time points. Qian et al simulated both circumstances (the sun at 12 pm and the moving pattern of the sun during a day) [38]. They found that the conclusion for the treatments were the same, regardless of if the sun position was fixed at 12 pm or changing over the day.…”
Section: The Effect Of Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The climate in these greenhouses cannot be better controlled for cultivation and the potential cucumber yield and quality cannot be exhibited. In recent years, a large number of Venlo-type greenhouses have been introduced in China, which improved the greenhouse climate and cucumber yield [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In the east and north of China, the combination of chilling and low irradiance in winter is the typical limiting factor for the growth and development of most greenhouse crops, such as tomato and cucumber, originating from tropical and subtropical regions (Hu et al 2006, Qian et al 2020, Zhang et al 2020b. Photosynthesis is the major physiological metabolic process inhibited at chilling temperatures (Allen and Ort 2001).…”
Section: Introductionmentioning
confidence: 99%